Effects Of Obesity On The Risk Of Mechanical Ventilation, Mortality, Survival Rate And Post Covid-19 Symptoms Among Hospitalized Covid-19 Patients At Tertiary Care Hospitals Of Hyderabad And Karachi, Pakistan - Qureshi, Ali (2024)
The covid-19 virus has affected a huge population of the world, including more than 3 million mortalities across the globe till 2020. The case fatality rate as of december 2020 was 2.29% in pakistan. In parallel with covid-19, another huge challenge to the global health community is the prevalence of obesity. Obesity is a known risk factor for severe covid-19 infection. In many cases it can leads to hospitalization, intensive care admissions, mechanical ventilation, and eventually death. Many individuals who recovered from the acute phase of the sars-cov-2 infection face long lasting symptoms which includes cognitive impairment, sleep trouble, exercise intolerance, and autonomic complaints. This condition is known as post-covid-19 syndrome. The aim of this study was to explore the effects of obesity on the risk of mechanical ventilation, mortality, survival rate and post covid-19 symptoms among hospitalized covid-19 patients at tertiary care hospitals of hyderabad and karachi, pakistan. This multicentered research was conducted at two public sector hospitals of sindh, pakistan. The study was accomplished in two phases, which were the retrospective phase conducted from march to december 2020 and the prospective phase conducted from january to july 2021. Survival analysis including survival function curve and cox-proportional hazards regression was conducted to determine the impact of obesity on survival rate.